(3GdebOeI GdBLQhejIs - (3GdUfgGLj, GHf BLQhe, CHh YHO Gddg, eMeO Hf YHO Gddg Hf OGhO, (B723 (3g`s ((3eMeO Hf Ydj GdehShjs)
(3ChdgG (B:s
(3GdMeO ddg (B.. (3HGH GdcdGe gh GddaX GdeQcH GdeajO HGdhVY hCbSGeg KdGKI GSe haYd hMQa LGA deYfi aGdGSe jYQa HGdLQ hGdJfhjf hONhd GdCda hGddGe hMQha GdNaV hgj ef hEdi hYf hYdi haj hMJi hQH (B...s
(3BNQgG (B:s
.. (3aGdfMh Yde jYQa Hg CMhGd ChGNQ GdcdeGJ EYQGHG hHfGA hGdcdeI GSe haYd hMQa hgj EeG JYed Ch dG JYed Gh JYed hJYed Ch dG JYed hdG JYed hGdYhGed efgG JJfhY YTQjf fhYG SeGYjI hbjGSjI hGdSeGYjI KdGKI YTQ fhYG hGdbjGSjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\33s
(3cTa GdXfhf (B2\1797s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs